2017
DOI: 10.1039/c7mb00488e
|View full text |Cite
|
Sign up to set email alerts
|

The Henipavirus V protein is a prevalently unfolded protein with a zinc-finger domain involved in binding to DDB1

Abstract: Henipaviruses are severe human pathogens within the Paramyxoviridae family. Beyond the P protein, the Henipavirus P gene also encodes the V protein which shares with P its N-terminal, intrinsically disordered region (PNT) and possesses a unique C-terminal domain predicted to be folded and to bind zinc (ZnFD). Henipavirus V proteins antagonize IFN signaling through PNT-mediated binding to STAT1, and several paramyxoviral V proteins promote STAT1 degradation through binding to DDB1. Structural and molecular info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…This activity relies on the ability of their V protein to bind to DNA damage-binding protein 1 (DDB1), a component of the ubiquitin ligase E3 complex, and then to recruit STAT proteins onto this complex [22]. In line with this, we have recently reported that Henipavirus V proteins interact with DDB1, and have unveiled a critical contribution of their C-terminal domain [23]. Incidentally, we also confirmed that the latter is folded and has a high β content both in isolation and when appended to PNT.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…This activity relies on the ability of their V protein to bind to DNA damage-binding protein 1 (DDB1), a component of the ubiquitin ligase E3 complex, and then to recruit STAT proteins onto this complex [22]. In line with this, we have recently reported that Henipavirus V proteins interact with DDB1, and have unveiled a critical contribution of their C-terminal domain [23]. Incidentally, we also confirmed that the latter is folded and has a high β content both in isolation and when appended to PNT.…”
Section: Introductionmentioning
confidence: 80%
“…Out of the two already available HeV domains (i.e. ZnFD and PNT) [8,23], only PNT was found to be able to form a hydrogel under conditions similar to those used for HeV V (Figure 1C). We subsequently divided the HeV PNT domain in four overlapping fragments (referred to as PNT1-PNT4) of 110 residues each ( Figure 1A).…”
Section: Liquid-hydrogel Transitions By the Hev V Protein And Identifmentioning
confidence: 96%
See 2 more Smart Citations
“…The crystal structures of NiV PMD (PDB code 4N5B) 8 and of the NiV N°-P NTD complex (PDB code 4CO6) 4 are shown. The homology-derived models of NiV XD 9 and of the ZnFD of V are also shown 10 . All structures were drawn using Pymol 2.0.1 (https ://pymol .org/2/) 11 .…”
mentioning
confidence: 99%